Ambedkar's illegal marriage: Hindu nation, Hindu modernity and the legalization of intercaste marriage in India. Issue 2 (4th May 2022) - Mandal, Saptarshi
ABSTRACT: Intercaste marriage is widely seen as an instrument for and an index of social equality. This article makes two interventions aimed at interrogating this perception. First, it shows that legalizing intercaste marriage became politically viable owing to its promise of modernizing Hindu marriage and fostering Hindu solidarity. Second, by turning to the anti-caste thought of B.R. Ambedkar, it shows that rather than prescribing intercaste marriage, as many scholars tend to claim, Ambedkar underscores its "futility" in the struggle for a casteless society. Removal of caste restrictions on marriage gave Hindus freedom in spouse selection, but left the material basis of caste unaltered. The article argues that the story of legislating this freedom bears out Ambedkar's thesis that pursuing freedom in the negative sense in a caste society does little to destroy caste.